Familial Risk Factors and Emotional Problems in Early Childhood: The Promotive and Protective Role of Children’s Self-Efficacy and Self-Concept - Sticca, Fabio; Wustmann Seiler, Corina; Gasser-Haas, Olivia (Frontiers in Psychology, 2020)
The present study aimed to examine the promotive and protective role of general self-efficacy and positive self-concept in the context of the effects of early familial risk factors on children’s development of emotional problems from early to middle childhood. A total of 293 (T1; Mage = 2.81), 239 (T2; Mage = 3.76), and 189 (T3; Mage = 9.69) children from 25 childcare centers took part in the present study. Fourteen familial risk factors were assessed at T1 using an interview and a questionnaire that were administered to children’s primary caregivers. These fourteen familial risk factors were used to compute a familial risk factors score. Primary caregivers also reported on their children’s emotional problems at T2 and T3 and on their children’s general self-efficacy at T2. Children reported on their positive self-concept at T2. Results showed that early familial risk factors were positively associated with emotional problems in the short and long term, although the long-term effect was small and non-significant. Further, the pattern of effect sizes of both promotive and protective effects of general self-efficacy as well as positive self-concept was found to be consistent in the short term. However, in the long term, no consistent support for either the promotive or the protective role of general self-efficacy or positive self-concept was found. These results suggest that general self-efficacy and positive self-concept might contribute to promote mental health and to protect from undesired effects of familial risk factors in the short term. Possible reasons for a lack of long-term effects are discussed along with practical implications.